(untitled) (Bangladesh Journal of Medical Education, 2022)
Introduction: This cross sectional study was conducted to identify the views of teachers of Surgery and its Allied Subjects about the present status of ‘Allied Subjects of Surgery’ in undergraduate medical education of Bangladesh. The study was conducted from January 2021 to December 2021. Methods: A self-administered semi-structured questionnaire was administered to collect data from 160 teachers of Surgery and its Allied Subjects. Convenience sampling technique was adopted for selection of eight medical colleges and the respondents were selected from the colleges purposively. Results : Study revealed that the contents and time allocated in the curriculum for the Surgery and its Allied Subjects were satisfactory but actual teaching hours and different teaching learning issues like number of teachers, lecture classes, tutorial classes, bedside teaching, evening clinical teaching, teaching at operation theater, teaching at emergency and casualty were poor in different Allied subjects of Surgery compared to General Surgery, Otolaryngology and Ophthalmology; and these differences were statistically significant in all most all cases. Conclusion: Hence it can be recommended that newer Allied Subjects of Surgery should get optimum importance during teaching learning in undergraduate medical education of Bangladesh. Bangladesh Journal of Medical Education Vol.13(2) July 2022: 35-41